1985
DOI: 10.1037/0022-3514.48.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and directed visual imagery: Image failure and image substitution.

Abstract: Both spontaneous and instructed imagery-based therapies have in common two types of image disparity, image failure, and image substitution. The alleged objectifying properties of emergent uncovering psychotherapy suggested that Freud's conception of repression and derivative formation applies to image disparity in each type of therapy. Subjects were asked to visualize the scenes of three stimulus narratives (two aggressive and one affectively neutral but implausible) and to signal successful visualization or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Additional research indicates that people are similarly disinclined to fantasize about negative outcomes. For example, Suler and Katkin (1988) demonstrated that subjects imaging fearful stimuli showed significant decrement in their ability to image as compared to subjects imagining nonfearful stimuli (see also Moses & Reyher, 1985;Wade, Malloy, & Proctor, 1977). Thus, it would be more likely for subjects to fantasize about generally positive alternatives as opposed to generally negative alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research indicates that people are similarly disinclined to fantasize about negative outcomes. For example, Suler and Katkin (1988) demonstrated that subjects imaging fearful stimuli showed significant decrement in their ability to image as compared to subjects imagining nonfearful stimuli (see also Moses & Reyher, 1985;Wade, Malloy, & Proctor, 1977). Thus, it would be more likely for subjects to fantasize about generally positive alternatives as opposed to generally negative alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Even when verbal information triggers mental imagery, people are less likely to engage in mental imagery if the information relates to negative stimuli (Moses & Reyher, 1985). In a product evaluation study with only verbal product descriptions, consumers who received instructions to imagine engaged in less mental imagery if the attributes were not pleasant to imagine (Keller & McGill, 1994).…”
Section: Pleasantness In Imaginingmentioning
confidence: 99%
“…Crits-Christoph and Singer (1983) look specifically at the use of positive imagery in the treatment of phobias. Moses and Reyher (1985) explore the use of directed versus spontaneous imagery in an experimental study and provide implications for psychotherapy. Grove (1989) is a model of metaphor-based treatment that is applied to resolving traumatic memories.…”
Section: The Rough and Tumble Mind: Where We Go To Play With Imagesmentioning
confidence: 99%